Evaluation of Disinfectants to Prevent Clavibacter michiganensis subsp. michiganensis Transmission in Tomato by Pruning Shears - Maeso, Diego; Walasek, Wilma (Agrociencia Uruguay, 2015)
Bacterial canker caused by Clavibacter michiganensis subsp. michiganensis (Cmm) is one of the most important tomato diseases in Uruguay. Its control is based on the use of pathogen-free seed and the transmission prevention during cultural practices. The objective of this work was to compare different disinfectants to prevent Cmm transmission by shears. In one experiment shears were immersed in a bacterial suspension while in the other, they were used in diseased plants. In both trials, healthy plants were then cut once with shears dipped in different disinfectants. Treatments included: 1) an inoculated control without disinfection, 2) a non-inoculated control, 3) sodium hypochlorite (1 % active chlorine), 4) potassium peroxymonosul-fate, 1 % solution (Virkon S®), 5) a 0.15 % solution of tensoactive agents complexed with iodine (Perrin iodine-based disinfectant), and 6) a 1 % solution of didecyldimethylammonium chloride (Sporekill®). A randomized complete block design with six replications was used with 20 plants per plot. Percentage of diseased plants was assessed by visual symptoms, bacterial isolation and serology. Shear disinfection with sodium hypochlorite solution (1 % active chlorine) Virkon S®, and Sporekill® managed to significantly reduce the levels of infection with Cmm; while iodine was not effective. Even though the number of infected plants decreased significantly, none of the treatments completely prevented transmission; suggesting that this measure should be complemented in an integrated management of the disease.